Brain-Computer Interface Research A State-of-the-Art Summary 3 - Guger, Christoph; Vaughan, Theresa; Allison, Brendan (SpringerBriefs in Electrical and Computer Engineering, 2014)
This book provides a cutting-edge overview of the latest developments in Brain-Computer-Interfaces (BCIs), reported by leading research groups. As the reader will discover, BCI research is moving ahead rapidly, with many new ideas, research initiatives, and improved technologies, e.g. BCIs that enable people to communicate just by thinking - without any movement at all. Several different groups are helping severely disabled users communicate using BCIs, and BCI technology is also being extended to facilitate recovery from stroke, epilepsy, and other conditions. Each year, hundreds of the top BCI scientists, engineers, doctors, and other visionaries compete for the most prestigious honor in the BCI research community: the annual BCI Award. The 2013 BCI Award competition was by far the most competitive, with over 160 research groups vying for a nomination. The chapters of this book summarize the ten projects that were nominated, in particular the winning project, and analyses how these reflect general trends in BCI development. Each project summary includes an introduction, description of methods, results, and also includes newer work completed after the project was entered for the competition. The texts are presented in accessible style with numerous supporting pictures, graphs, and figures.